Byrsonima fagifolia: An integrative study to validate the gastroprotective, healing, antidiarrheal, antimicrobial and mutagenic action - Lima, Zeila Pinheiro [UNESP]; dos Santos, Raquel de Cassia [UNESP]; Torres, Talita Uliana [UNESP]; Sannomiya, Miriam [UNESP]; Rodrigues, Clenilson Martins [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Pellizzon, Claudia Helena [UNESP]; Machado Rocha, Lucia Regina [UNESP]; Vilegas, Wagner [UNESP]; Monteiro Souza Brito, Alba Regina; Primila Cardoso, Cassia Regina [UNESP]; Varanda, Eliana Aparecida [UNESP]; et al. (Elsevier B.V., 2008)
Ethnopharmacological relevance: Ethnopharmacological survey indicated leaves of Byrsonima fagifolia Nied. (Malpighiaceae) against gastrointestinal disorders.Aim of the study:The methanolic extract from the leaves of Byrsonima fagifolia (denominated BF)was evaluated for toxic, mutagenic, gastroprotective, antidiarrheal, antibacterial and immunomodulatory activities. Materials and methods: The preventive and healing action of BF against gastric ulcer was evaluated in experimental models in rodents. We evaluated immunomodulatory (by murine peritoneal macrophages), antidiarrheal (by induced diarrhea with castor oil and intestinal motility) and antibacterial action of BF against standard strain of Escherichia coli, Staphylococcus aureus and Helicobacter pylori. The safety of use of BF was also evaluated by mutagenic (Ames assay) and by analyses of toxicity parameters.Results: Phytochemical BF profile indicated the presence of phenolic compounds with antioxidant and radical-scavenging properties. BF significantly inhibited gastric lesions induced by ethanol and HCl/ethanol and endogenous mucosal sulphydryl groups (SHs) participated efficaciously in BF gastroprotection. of blocked development of inflammation process and also has antidiarrheal actions. This extract accelerated the healing of the gastric ulcerated mucosa by stimulating proliferative factors and by increasing production of gastric mucus with no toxic action. The substances responsible for the protective action are concentrated in the ethyl acetate fraction that demonstrated no mutagenic action in vitro.Conclusions: Byrsonima fagifolia presents gastroprotective, healing and antidiarrheal activities supporting previous claims that its traditional use by Brazilians can treat these gastrointestinal ailments. Published by Elsevier B.V.
Keywords: Byrsonima fagifolia; Malpighiaceae; Healing effect; Antidiarrheal action; Mutagenicity